Anesthesia for Patients with Prior Stroke - Karnik, Hemangi Sanjay; Jain, Ruchi Arunkumar (Journal of Neuroanaesthesiology and Critical Care, 2018)
An increasing number of patients with a prior history of stroke present for various types of surgeries. They have varying degree of neurological disability and associated co-morbidities, which pose challenges for their perioperative management. There is paucity in literature about their management guidelines for noncardiac, noncarotid surgeries. The available literature suggests higher risk of perioperative stroke, postoperative neurological deficits, and other morbidities. Measures to reduce perioperative risks are discussed in this review. Prior optimization by improving modifiable risk factors, choosing appropriate timing of elective surgery, and careful titration of anesthesia and close monitoring are needed.
Keywords: stroke; anesthesia; perioperative risk; cerebral ischemia